General strain and procedural justice in retail banking: A qualitative case study with a multi-theoretical approach to improving compliance policy. Issue 3 (4th July 2016) - Leasure, Peter
Abstract : Purpose: The purpose of the current study is to examine the applicability of general strain and procedural justice theories to retail banking deviance in an effort to improve compliance programs. Design/methodology/approach: This objective is achieved through a qualitative case study of active members of the retail banking industry guided by three research questions. First, how do participants view their companies' current compliance programs? Second, what types of crime or deviance are present in the data in which general strain and procedural justice theories are indicated? Third, what ethics and compliance recommendations can be made from the identified deviance and underlying theories? Findings: Results indicate that current ethics and compliance programs are viewed as having serious flaws. Results also show the presence of a large amount of fraud based deviance in which both general strain and procedural justice theories seem to be implicated. Specific compliance enhancements are proposed in light of these findings. Originality/value: The current study is one of the first to examine white collar crime deviance and ethics and compliance programs in the retail banking industry. Conducting research in specific industries is key as findings from a study in a particular industry may not extrapolate to another. Further, the current study uses a qualitative approach, which allows a deeper understanding of underlying mechanisms, with participants who have committed some form of deviance and are active members in their industry. Because of this fact, this study has the potential to provide new and different insights than a study conducted using students or other such participants and hypothetical scenarios.